The Effect of Adversity Quotient on Learning Outcomes of Buddhist Religious Education at Junior High School - Indi Sukmawati; Komang Sutawan; Taridi Taridi; Ria Astika; Tejo Ismoyo; Sutiyono Sutiyono (Universitas Sebelas Maret, 2024)
This study aimed to find the effect of adversity quotient intelligence on the learning outcomes of Buddhist religious education. The problems that occur in students are that there are students who admit that they have never received a ranking, rarely study at home, and there are also students who cannot focus for a long time when studying, and the teaching method is less effective. In addition, learning carried out by teachers is still primarily done conventionally, and the lack of learning facilities is also the cause of weak student learning motivation in carrying out the learning process. This study uses a quantitative approach with a survey method. The population in this study was 133, with a sample of 100 obtained by the Proportional Random Sampling sampling technique. The study results showed a significant adverse effect between adversity quotient intelligence on the learning outcomes of Buddhist religious education with a t count of -3.804 and a significance value (p) of 0.000 <0.05. From the results of the simple regression analysis calculation, the R Square value was obtained at 0.136. This means that adversity quotient intelligence influences the learning outcomes of Buddhist religious education by 13.6%, and other factors influence the remaining 86.4%. The adversity quotient value measures an individual's ability to handle and overcome challenges. Students with high AQ may feel burdened if students face challenges or difficulties in the learning process regularly. Excessive stress and fatigue can harm learning outcomes.